Validitas dan Reliabilitas Instrumen Tes Kemampuan Komunikasi Matematis Materi Relasi Dan Fungsi - Vera Wahyuni (Sustainable, 2022)
The test instrument is one aspect of the learning process that is used to produce learning outcomes or the level of knowledge of students. The research method used in this research is descriptive quantitative research. The population in this study were all students of class VIII SMP Negeri 1 PGRI Batanghari which consisted of 5 classes, with research samples namely class VIII B and class VIII A, the results of this study showed content validity based on experts with an average V index of more than 0,3 then for empirical validity 14 of 15 are declared valid with an average result of more than 0.3, then the reliability test shows the results of 0.740 > 0.6 so it can be said that a valid and reliable mathematical communication ability test is used to measure communication skills mathematics relational materials and functions